Comparative clinical outcomes of full-endoscopic posterior lumbar interbody fusion, biportal endoscopic posterior lumbar interbody fusion, and conventional posterior lumbar interbody fusion in the treatment of lumbar degenerative diseases - Zhao, Hongshun; Zhou, Shihao; Su, Xinliuyue; A, Jiancuo; Xu, Zhihua; Wei, Ying; Hao, Yan; Wang, Yu; Wang, Chengfu; Ma, Jiwei (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to evaluate and compare the clinical efficacy of three surgical procedures for lumbar degenerative disease (LDD): full-endoscopic posterior lumbar interbody fusion (Endo-PLIF), biportal endoscopic lumbar interbody fusion (ULIF), and conventional posterior lumbar interbody fusion (PLIF). This comparison was intended to inform and support clinical decision-making.MethodsA total of 193 patients diagnosed with LDD were enrolled between January 2021 and July 2023. Among them, 63 underwent ULIF, 73 received Endo-PLIF, and 57 underwent PLIF. The collected variables included patient demographics, incision length, length of hospital stay, and changes in both disc height and foraminal height. Outcomes were assessed using the Visual Analog Scale (VAS), Oswestry Disability Index (ODI), modified MacNab criteria, fusion rate, and the incidence of complications. Descriptive statistics and multiple group comparisons were conducted to analyze intergroup differences. Generalized mixed linear models were applied to assess longitudinal outcomes.ResultsThere were no statistically significant differences in preoperative VAS scores among the three groups (P > 0.05). On postoperative day 3, VAS scores for back pain were significantly lower in the ULIF group compared to the Endo-PLIF and PLIF groups (P < 0.001). At 3 months and during long-term follow-up, VAS scores showed no significant differences among the groups. ODI scores in the ULIF group were significantly lower than those in the other two groups (P = 0.004). At final follow-up, modified MacNab ratings showed no significant differences among the groups. All three surgical techniques provided effective symptom relief and were associated with favorable clinical outcomes.ConclusionThis study provides important insights into the clinical efficacy of ULIF, Endo-PLIF, and PLIF in the treatment of lumbar degenerative diseases. Although ULIF demonstrates superior outcomes in terms of early postoperative pain control and functional recovery, the long-term results are similar across the three techniques. Spine surgeons can make individualized decisions regarding the choice of surgical approach based on specific patient factors, such as disease severity, comorbidities, and recovery goals.